Use of Fulltext Indexing to Improve Data Search Efficiency in MYSQL Databases - Ahmad Hajar; Ema Utami; Hanif Al Fatta (STMIK PONTIANAK, 2022)
The process of searching for data is one of the needs of the system that is needed. With the more data, the search process will take longer. There are many ways to speed up the data search process, one of which is by utilizing the Full text index feature in the MySQL database. In this study, a search query will be tested on tables that have been indexed and on tables that have not been indexed. Researchers use the like operator to search for data on tables that are not indexed. Meanwhile, in the table given the index, the researcher uses a full text search with the match against syntax. The results of this study indicate that the full text search on a table that has been given an index is faster than a table that is not indexed. When the number of data is 466,000, searching in a non-index table takes 2,638.97 milliseconds. Meanwhile, the indexed table takes 89.14 milliseconds. Then the impact of giving an index to the table is that the insert process takes longer than the table that is not indexed. In the product index table when the data is 466,000, the insert time is 6,560.69 milliseconds. While the product non index table is 420.96 milliseconds. In future research, it is expected to look for other query testing methods and find out the accuracy between like operator and match against.